Therapeutic implications of inhibition versus killing of Mycobacterium avium complex by antimicrobial agents. - Yajko, D M (1987)
Patients with the acquired immune deficiency syndrome (AIDS) with disseminated Mycobacterium avium infection have responded poorly to treatment with rifabutine (Ansamycin) and clofazimine, in spite of the good in vitro response of M. avium to these antimicrobial agents. We compared the ability of these and other antimicrobial agents to kill versus the ability to inhibit the growth of strains of the M. avium complex isolated from patients with AIDS. Killing curve experiments showed that the concentrations of rifabutine and clofazimine needed to kill two log units of M. avium are at least 32 times greater than the concentrations needed to inhibit growth. Little or no killing occurred at concentrations of these antimicrobial agents that are achievable in serum. In contrast, five of seven strains tested were killed by ciprofloxacin at concentrations that can be achieved in serum. Ciprofloxacin should be studied further for possible use in the treatment of M. avium infections.